Government Expenditure on Future Graduates in South African Higher Education - Folasade, Oladele Musili; Mahlaule, Calvin; Ifunanya, Nwosu Lilian (International Journal of Economics and Financial Issues, 2026)
Education is crucial for a nation's welfare, economic and social development, and advancement. Government spending on higher education in South Africa could significantly impact the employment and social mobility of future graduates. The 2015 to 2016 student protests, sparked by rising tuition prices and decreased government financing, highlighted the industry's vulnerability to social and economic forces. Higher education is seen as the vanguard of this movement, with the knowledge and skills graduates acquire enhancing their employability and income. Governments allocate a large portion of their finances to education, expecting it to indirectly benefit students. This study examines the influence of government spending on future graduates in South African higher education, the financing deficit, and the effects on affordability, quality, and accessibility. The study adopted annual time series data from 1983 to 2023. The study used Autoregressive Distributive Lag (ARDL), and ECM techniques. The results indicate a long-term correlation between government investment and education, which is important when considering the effects on future graduates. The study also found that social mobility and employability are two areas governments need to improve in the higher education system. Higher education institutions must also improve the welfare of future graduates, including their business acumen and readiness for the economy.